2007
DOI: 10.1007/978-3-540-72990-7_70
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interference on Optimal Multi-path Routing in Ad Hoc Networks

Abstract: We develop a queueing model characterizing explicitly the impact of interference on end-to-end performance measures such as throughput in ad hoc networks, emphasizing the performance trade-off between single-path and multi-path routing. It may seem attractive to employ multi-path routing, but as all nodes share a single channel, efficiency may drop due to increased interference levels thus yielding single-path performance for some topologies. We formulate a nonlinear programming problem to optimize network per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…• Previous work [7][8][9] does not provide a solution to discover multiple paths, though it discusses how to determine sustainable throughput when using multipath. This paper introduces two different criteria to select multiple paths: interference between paths and BTL in a path.…”
Section: Related Workmentioning
confidence: 98%
See 3 more Smart Citations
“…• Previous work [7][8][9] does not provide a solution to discover multiple paths, though it discusses how to determine sustainable throughput when using multipath. This paper introduces two different criteria to select multiple paths: interference between paths and BTL in a path.…”
Section: Related Workmentioning
confidence: 98%
“…In the previous work, analysis of behaviour of different types of multipath routes is not done except in Reference [9], but it analyses scenarios without considering BTL.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that adopting interference reduction measures can bring in improvement in the throughput. [18] presents a stochastic framework for analysis of interference and develops a mathematical model to assess network capacity for multipath routing using non linear programming. But these methods proves to be inefficient even for small networks due its complexity .…”
Section: Related Workmentioning
confidence: 99%